Biosolids effects on earthworm survival and the bioaccumulation of Triclosan in the earthworm Esenia Foetida - Clarke, B.; Duke, W.; Linge, Kathryn; Majer, Jonathan; Pritchard, Deborah; Penney, N. (Australia Water Association, 2012)
Triclosan is a ubiquitous contaminant in Australian biosolids and the land application of biosolids is potentially a significant source of environmental exposure. Triclosan has been identified as a concern due to the potential tobioaccumulate and biomagnify in food chains. To examine this issue a study was developed to investigate the impacts of triclosan (from biosolids) upon the survival and health on the earthworm Eisenia fetida. This study was completed as part of a third year student research project at Curtin University. Artificial test soil was augmented with four biosolids application rates (1A-, 2A-, 3A- and 4A-) where the nitrogen limited biosolids application rate (NLBAR) was used as the base rate. All treatments, including the control, were prepared in triplicate. Triclosan concentrations were measured in biosolids, soil and earthworms using GC/MS techniques. Triclosan was found to accumulate in earthworms having a concentration of 1 .8 A± 0.54 ug/g wet weight. The biosolids used in this study had a concentration of 5.0 A± 0.79 ug/g and this is low compared to other studies. These findings indicate that the earthworm Eisenia fetida feeds on biosolids that contain triclosan and that the triclosanis bioaccumulated in their tissues. Many studies have investigated the effects on human health to organic contaminants present in biosolids, however, few studies have investigated the exposure of soil biota to organic contaminants following the land application of biosolids. This study is the first of a series of work that aims to explore the issue of ecological risks posed by organic pollutants when applying biosolids to agricultural land .